2017
DOI: 10.14348/molcells.2017.0015
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Regulatory Domain of AphB from Vibrio vulnificus, a Virulence Gene Regulator

Abstract: The transcriptional activator AphB has been implicated in acid resistance and pathogenesis in the food borne pathogens Vibrio vulnificus and Vibrio cholerae. To date, the full-length AphB crystal structure of V. cholerae has been determined and characterized by a tetrameric assembly of AphB consisting of a DNA binding domain and a regulatory domain (RD). Although acidic pH and low oxygen tension might be involved in the activation of AphB, it remains unknown which ligand or stimulus activates AphB at the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Applying PGSEA on miRNA target genes highlights miRNA-30a (Additional file 3: Figure S20), whose target genes are specifically activated by IR in wild-type B cells. miRNA-30a was shown to be involved in response to IR [77] and mutually regulate p53 [78]. Thus, the complex p53 signaling pathways are unveiled with remarkable accuracy.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Applying PGSEA on miRNA target genes highlights miRNA-30a (Additional file 3: Figure S20), whose target genes are specifically activated by IR in wild-type B cells. miRNA-30a was shown to be involved in response to IR [77] and mutually regulate p53 [78]. Thus, the complex p53 signaling pathways are unveiled with remarkable accuracy.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Both residues are found far from the DNA binding site, but while K271 is located on the back relative to the dimerization interface, the K103 was in a position to potentially affect dimerization (Figure 7A ). In the Vibrio vulnificus AphB homolog, K103 was shown to interact with an as yet unknown ligand (Park et al, 2017 ). Acetylation of vibriobactin transporter VctP (KNH52012) K110 was identified in both growth conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The RD of LTTRs has an inducer binding cavity (IBC) and is presumed to play a critical role in the conformational change of the LTTR tetramer upon inducer binding (Choi et al, 2001;Maddocks and Oyston, 2008;Quade et al, 2011;Park et al, 2017). The RD from CysB was the first crystal structure solved of a RD (Tyrell et al, 1997).…”
Section: Regulatory Domain (Rd)mentioning
confidence: 99%
“…RD-II contains a five-stranded -sheet that is strongly twisted and four -helices ( Fig. 4) (Tyrell et al, 1997;Muraoka et al, 2003;Monferrer et al, 2010;Quade et al, 2011;Park et al, 2017). Structural studies of BenM, OxyR, PcaQ, RovM, AphB and DntR have led us to hypothesize that inducer binding (or environmental change) to the RD of LTTR causes a conformational change in the RD that is propagated throughout the tetrameric LTTR and changes the bend angle of the promoter DNA (Kovacikova and Skorupski, 2001;Bundy et al, 2002;Smirnova et al, 2004;Quade et al, 2011;Wei et al, 2012;Jo et al, 2015) However, while crystal structures of OxyR (Choi et al, 2001;Jo et al, 2015), BenM (Ezezika et al, 2007a) and DntR (Devesse et al, 2011) have revealed conformational changes of the RD upon inducer binding, conformational changes of tetrameric full-length LTTR upon inducer binding have not been observed in the crystal.…”
Section: Regulatory Domain (Rd)mentioning
confidence: 99%
See 1 more Smart Citation